2022
DOI: 10.1021/acsmacrolett.2c00258
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Alternating Metathesis Copolymerization of Terminal Alkynes

Abstract: Terminal alkynes display high reactivity toward Ru-carbene metathesis catalysts. However, the formation of a less reactive bulky carbene hinders their homopolymerization. Simultaneously, the higher reactivity of alkynes does not allow efficient cross propagation with sterically less-hindered cycloalkene monomers, resulting in inefficient copolymerization. Nonetheless, terminal alkynes undergo rapid cross-metathesis with vinyl ethers. Therefore, an efficient cross propagation can be achieved with terminal alkyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…So far, there have been very few reports to grow ROMP polymers from a macromolecule using olen metathesis catalysts. [52][53][54] Functionalizing any metathesis catalyst using only one equivalent pre-functionalization agent attached to a polymer is exceedingly challenging. Given the speed and high regioselectivity of our CTAs, we anticipated that a monosubstituted 1,3 diene derivative attached to the chain end of a polymer could serve as a macroinitiator to initiate ROMP.…”
Section: Branched Romp Polymersmentioning
confidence: 99%
“…So far, there have been very few reports to grow ROMP polymers from a macromolecule using olen metathesis catalysts. [52][53][54] Functionalizing any metathesis catalyst using only one equivalent pre-functionalization agent attached to a polymer is exceedingly challenging. Given the speed and high regioselectivity of our CTAs, we anticipated that a monosubstituted 1,3 diene derivative attached to the chain end of a polymer could serve as a macroinitiator to initiate ROMP.…”
Section: Branched Romp Polymersmentioning
confidence: 99%
“…Afterward, the Gutekunst group reported an alternating cascade copolymerization of DHF and alkynes. , A very recent report showed the synthesis of degradable polymers via ROMP of DHF with norbornene derivatives . Our group has also reported alternating metathesis copolymerization of DHF with terminal alkynes . However, in all these cases, just like in conventional living ROMP, a stoichiometric amount of ruthenium initiator with respect to the polymer chains is required.…”
Section: Introductionmentioning
confidence: 96%
“…26 Our group has also reported alternating metathesis copolymerization of DHF with terminal alkynes. 27 However, in all these cases, just like in conventional living ROMP, a stoichiometric amount of ruthenium initiator with respect to the polymer chains is required. This often leads to high catalyst loadings, which is quite expensive, as well as difficult as far as removing the toxic metal contaminants from the synthesized polymers is concerned.…”
Section: ■ Introductionmentioning
confidence: 99%
“…An attractive method of addressing sustainability in thermosets is to incorporate cleavable units into the strands of the polymeric network. , Shieh et al recently demonstrated the ring-opening metathesis polymerization (ROMP) of p­(DCPD) thermosets having cleavable siloxane repeat units in the strands of the network. , Polymer backbone deconstruction was triggered with a fluoride reagent. Similar strategies have focused on generating thermoplastics utilizing cleavable cyclic olefin comonomers containing acetal, disulfide, phosphoramidite, carbonate, and enol ether moieties. Recent work from the Xia group demonstrated the synthesis of cleavable thermoplastics via the copolymerization of 2,3-dihyrdofuran (DHF) with a variety of norbornene derivatives. In addition to functioning as a cleavable unit, DHF suppressed the reactivity of Grubbs catalyst (GC) .…”
Section: Introductionmentioning
confidence: 99%